The investigation of the students’ attitude and consciousness degree regarding the pregnancy health in 2013 in Eastern-Azerbaijan Province - Pour, Robab Kazem; Vakilian, Katayun (Journal of Research in Biology, 2017)
The purpose of this research was to investigate the students’ attitude and consciousness degree regarding the pregnancy health in 2013 in Eastern-Azerbaijan Province. So, 300 students in different semesters have been taken up as accidentally from Tabriz, Marand, Bonab, Maragheh and Ahar have been taken up in this study. The WHO illustrative questionnaire for interview-questionnaire designed by John Cleland surveys with young people has been applied in this study. The statistical data has been completed by the help of SPSS software and descriptive and t-test statistical cases. The results showed the attitude score from the family adjustment is significantly higher than the determined degree positively. The results showed the sexual diseases are significantly higher than the fixed determined degree positively. Also it showed there is no observed any significant difference between the degree of the conscious and the students’ attitude based on their marital status The results did not show any significant difference regarding the degree of the attitude among students.